The 26th Constitutional Amendment in Pakistan: A Threat to Judicial Independence and Democratic Governance - Muzamil Ali; Dr. Tansif Ur Rehman; Aliya Saeed (Indus Journal of Social Sciences, 2025)
In October 2024, Pakistan adopted the 26th Constitutional Amendment that encompassed various controversial provisions on the judicial system in that country. This Amendment had a new process of appointing the Chief Justice by a parliamentary committee, restricted the suo motu power of the judiciary, and comprised political leaders in the Judicial Commission of Pakistan. Although the government defended these reforms by saying that they were needed to make their system efficient, the critics are of the view that they threaten the sovereignty of the judiciary and are an assault on the concept of separation of powers that was featured in the Constitution. The Amendment was hurriedly put across without proper discussion in parliament and the involvement of key players, which casts doubts on transparency and adherence to democratic conventions. The Human Rights Commission of Pakistan and the International Commission of Jurists have gone ahead to criticize the Amendment to the extent that they termed it unconstitutional and politically-driven. The paper is a critical review of the text of the Amendment, legal implications, and the political context of the same, which will conclude that the Amendment is a great threat to judicial independence and democracy in Pakistan.